Gallbladder Adenoumatous Polyps prevelance in Cholcystectomy in Saudi Arabia-cross sectional study - Mohammad Alharbi (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Introduction: Gallbladder polyps (GP), especially adenomatous, is quite rare. The prevalence of GP globally is variable, its importance comes from its potential to progress to gallbladder adenocarcinoma. Methods: Cross sectional study of patients who had laparoscopic cholecystectomy, March 2009-sept 2017 in a community hospital in sulayel area in Saudi Arabia, to evaluate the prevalence of adenomatous gallbladder polyps in the pathology specimens. Results: The prevalence of adenomatous gallbladder polyps is approaching 0.4% ,no foci of malignancy were found. It is still below the international prevalence rate. 107 (8.9 %) patients with acute cholecystitis, 119 (9.9 %)acute on chronic cholecystitis, 11 (0.9 %) with complicated cholecystitis and 968 (80.3 %) patients with chronic cholecystitis. Discussions: The prevalence of adenomatous gallbladder polyps is approaching 0.4%, no foci of malignancy were found. It is still below the international prevalence rate.  Conclusion: Low prevalence rate of adenomatous gallbladder polyps compared to international levels may need further studies to explore the reasons behind.